K-dependent inhibition in the dentate-CA3 network of guinea pig hippocampal slices - Misgeld, Ulrich; Bijak, Maria; Brunner, Hans; Dembowsky, Klaus (Journal of neurophysiology, 1992)
1. The occurrence of potassium-dependent inhibitory postsynaptic potentials (K-IPSPs) in relation to burst discharges induced by 4-aminopyridine (4-AP; 30 microM) was studied in CA3, granule and hilar neurons in guinea pig hippocampal slices with the use of paired extra- and/or intracellular recording. 2. Slow small (2-5 mV) and large (up to 30 mV) K-IPSPs were observed in CA3, granule and in some hilar neurons during 4-AP applications in the presence of blockers for fast synaptic transmission, picrotoxin (50 microM), and 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX; 5-10 microM). Amplitudes of K-IPSPs were linearly related to voltage, and they reversed in sign close to -100 mV, as expected for synaptic potentials generated by an increase in K-conductance. 3. In CA3 neurons, 4-AP applied in the presence of picrotoxin elicited burst discharges and K-IPSPs. CNQX blocked the burst discharge activity and increased the amplitude of K-IPSPs. 4. In granule cells, 4-AP applied in the presence of picrotoxin elicited K-IPSPs and only inconsistently small excitatory postsynaptic potentials (EPSPs). The EPSPs were blocked by CNQX, but CNQX application did not affect the K-IPSPs. However, in granule cells it could be observed that blockade of Cl-inhibition by picrotoxin in the presence of CNQX increased the amplitude of K-IPSPs. 5. In hilar neurons, 4-AP applied in the presence of picrotoxin elicited mainly burst discharges. CNQX blocked the burst discharges only in a few cells. In most hilar neurons K-IPSPs were observed at the beginning of the 4-AP effect, but subsequently K-IPSPs were replaced by burst discharges. 6. To determine the type of cells that burst in picrotoxin and 4-AP, neurons were stained intracellularly with horseradish peroxidase. Neurons stained in the granule cell layer did not burst and were morphologically identified as granule cells. Neurons stained in the hilar region burst and were nonpyramidal, nongranule cells. Bursting cells stained in the CA3 area were all pyramidal cells. 7. The hilar neurons varied considerably in size and dendritic organization. They could be classified as aspiny and spiny cells, the latter including mossy cells. 8. We conclude that K-dependent inhibition may explain the long-lasting IPSPs observed in in vivo recordings from hippocampal cells. In a hippocampal lamella, burst discharge activity of hilar neurons including presumed excitatory mossy cells is associated with inhibition of granule cells.(ABSTRACT TRUNCATED AT 400 WORDS)